Fixed-Income Markets in the United States, Europe, and Japan-Some Lessons for Emerging Markets - Schinasi, Garry; Smith, T. (Washington, D.C. : International Monetary Fund, 1998)
This paper identifies factors that contributed to the development and effectiveness of debt securities markets in the major advanced economies. Government securities markets have benefited from their international orientation-debt management is most effective when it is independent of monetary and exchange rate policies; and financial infrastructures should be patterned on the standards of liquidity, transparency, issuing and trading efficiency, and tax treatment. The same degree of consensus does not exist for corporate debt securities markets. The paper identifies six regulatory and market-created factors that help explain why the U.S. corporate debt market has flourished, while corporate debt securities markets elsewhere have only recently begun to develop.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet